The protective effect of coffee consumption on cutaneous melanoma risk and the role of GSTM1 and GSTT1 polymorphisms - Fortes, Cristina; Mastroeni, Simona; Boffetta, Paolo; Antonelli, Gianluca; Pilla, Maria Antonietta; Bottà, Giordano; Anzidei, Patrizia; Venanzetti, Federica (Cancer causes & control, 2013)
Purposes: The authors examined the association between coffee consumption and cutaneous melanoma and the implication of GSTM1 and GSTT1 polymorphisms. Methods: A hospital-based case-control study was conducted in the inpatient wards of IDI-San Carlo Rome, Italy, including 304 incident cases of cutaneous melanoma and 305 controls. Information on socio-demographic characteristics, medical history, smoking, sun exposure, pigmentary characteristics and diet was collected for all subjects. Within the study, individual patterns at two polymorphic genes (GSTM1 and GSTT1) belonging to glutathione S-transferases family were investigated in 188 cases of cutaneous melanoma and 152 controls. Logistic regression was the method used to estimate odds ratio and 95 % confidence intervals. Results: High frequency of coffee drinking (>once daily), compared with low-frequency consumption of coffee (≤7 times weekly) was associated with a protective effect for cutaneous melanoma (OR 0.46; 95 % CI 0.31–0.68) after adjusting for sex, age, education, hair colour, common nevi, skin phototype, and sunburn episodes in childhood. When stratified by GSTM1 and GSTT1 genotype, the protective effect of coffee was extremely high for subjects with both GSTM1 and GSTT1 null polymorphisms (OR 0.01; 95 % CI 0.0003–0.54). Conclusions: Our results show a protective effect of coffee consumption for cutaneous melanoma, in particular for those with homozygous deletion for GSTM1 and GSTT1.